Antibiotic Resistance Patterns of Group B Streptococcal Clinical Isolates. Issue 1 (2004) - Simoes, Jose A.; Aroutcheva, Alla A.; Heimler, Ira; Faro, Sebastian
Abstract : Objectives: To determine the in vitro resistance of group B streptococcus (GBS) to 12 antibiotics. To determine if there has been any decrease in sensitivity to the penicillins or other antibiotics currently used for GBS chemoprophylaxis in pregnant women. Find suitable alternative antibiotics to penicillin. Find an antibiotic that will have minimal selective pressure for resistance among the endogenous resident vaginal microflora. Methods: The antibiotic susceptibility profiles of 52 clinical isolates of GBS were evaluated to 12 antibiotics: ampicillin, azithromycin, cefamandole, cefazolin, ceftriaxone, ciprofloxacin, clindamycin, erythromycin, nitrofurantoin, ofloxacin, penicillin and vancomycin. Antibiotic sensitivities were determined using disk diffusion and microdilution methods according to the guidelines of the National Committee for Clinical Laboratory Standards (NCCLS). Results: All isolates were sensitive to vancomycin, ofloxacin, ampicillin, ciprofloxacin, nitrofurantoin and penicillin. However, the following number of clinical isolates exhibited intermediate or decreased sensitivity, nine (17%) to ampicillin, eight (15%) to penicillin, 14 (32%) to ciprofloxacin and one (2%) to nitrofurantoin. Thirty-one percent of the isolates were resistant to azithromycin and ceftriaxone, 19% to clindamycin, 15% to cefazolin and 13% to cefamandole. Eighteen (35%) of the clinical isolates tested were resistant to 6 of the 12 antibiotics tested. Conclusions: The relatively high rates of resistance for 6 of the 12 antibiotics tested suggest that for women allergic to penicillin and colonized with GBS, antibiotic sensitivities to their isolates should be determined. The antibiotic selected for intrapartum chemoprophylaxis should be guided by the organism's antibiotic sensitivity pattern. Patients with GBS bacteriuria should be treated with nitrofurantoin.